Vehicle trajectory based control delay estimation at intersections using low-frequency floating car sampling data - Wang, Hua; Gu, Changlong (Transport, 2020)
Control delay is an important parameter that is used in the optimization of traffic signal timings and the estimation of the level of service at signalized intersection. However, it is also a parameter that is very difficult to estimate. In recent years, floating car data has emerged as an important data source for traffic state monitoring as a result of high accuracy, wide coverage and availability regardless of meteorological conditions, but has done little for control delay estimation. This article proposes a vehicle trajectory based control delay estimation method using low-frequency floating car data. Considering the sparseness and randomness of low-frequency floating car data, we use historical data to capture the deceleration and acceleration patterns. Combined with the low-frequency samples, the spatial and temporal ranges where a vehicle starts to decelerate and stop accelerating are calculated. These are used together with the control delay probability distribution function obtained based on the geometric probability model, to calculate the expected value of the control delay for each vehicle. The proposed method and a reference method are compared with the truth. The results show that the proposed method has a root mean square error of 11.8 s compared to 13.7 s for the reference method for the peak period. The corresponding values for the off-peak period are 9.3 s and 12.5 s. In addition to better accuracy, the mean and standard deviation statistics show that the proposed method outperforms the reference method and is therefore, more reliable. This successful estimation of control delay from sparse data paves the way for a more widespread use of floating car data for monitoring the state of intersections in road networks. First published online 5 February 2020